Effect of compliance and hematocrit on wall shear stress in a model of the entire coronary arterial tree - Huo, Yunlong (American Physiological Society, 2009)
A hemodynamic analysis is implemented in the entire coronary arterial tree of diastolically arrested, vasodilated pig heart that takes into account vessel compliance and blood viscosity in each vessel of a large-scale simulation involving millions of vessels. The feed hematocrit (Hct) is varied at the inlet of the coronary arterial tree, and the Fahraeus-Lindqvist effect and phase separation are considered throughout the vasculature. The major findings are as follows: 1) vessel compliance is the major determinant of nonlinearity of the pressure-flow relation, and 2) changes in Hct influence wall shear stress (WSS) in epicardial coronary arteries more significantly than in transmural and perfusion arterioles because of the Fahraeus-Lindqvist effect. The present study predicts the flow rate as a second-order polynomial function of inlet pressure due to vessel compliance. WSS in epicardial coronary arteries increases >15% with an increase of feed Hct from 45% to 60% and decreases >15% with a decrease of feed Hct from 45% to 30%, whereas WSS in small arterioles is not affected as feed Hct changes in this range. These findings have important implications for acute Hct changes under vasodilated conditions.